Barracas de Praia, praia de barracas: configuração, tipo e usos na praia do futuro, Fortaleza CE - Donegan, Lucy (2011)
The purpose of this dissertation is to analyse the importance of the huts of Praia do Futuro to their users and to the city of Fortaleza in Ceará through the comprehension of relations between morphological categories - in urban and edified contexts - of the establishments and their use patterns. This place is one of the main recreation and leisure areas of the city, formed by six kilometres of waterfront, corresponding to a differentiated area through the coast. This space has beach huts with varied profiles: while some more simple huts persist, great complexes are being developed, building even water parks on the beach area. This study analyses relations between:i) spatial configuration (in geometric and mainly topological terms) based on the Social Logic of Space; ii) edified typology (analysing capacity, landscap treatment and program of the huts); and iii) use and environmental perception of the beach by its frequenters. There are consistent relations between the type of hut and their localization in the urban grid, of which were identified groups with different patterns: segregated (north, central and south) and integrated (north: more integrated. and south: less integrated). Such relations also reflect, in varied patterns of use and environmental perception. In spite of their strong economy, the beach huts find themselves in a fragile legal situation because they occupy the beach area, so that this study may come to assist the decision-making for the future of the region. For a sustainable development of the area by those responsible and managers it is necessary to evaluate the cultural importance of the huts at Praia do Futuro, understanding their occupation and uses.